Efficient foundation pits solutions for restrained urban conditions - Vynnykov, Yuriy; Kharchenko, Maksym; Akopian, Mkrtich; Aniskin, Aleksej (Academic journal Industrial Machine Building Civil Engineering, 2022)
There are presented analysis results of the new multi-story residential building construction’s impact on the existing development, constructive and technological measures for the arrangement of an excavation, deeper than the existing foundations’ footing level, with minimal costs and minimal negative impact on the surrounding buildings. In particular, its excavation stages, results of the excavation shoring strength calculation, as well as proposals for the technical condition monitoring of existing buildings in the process of new construction were introduced. The calculation of the new construction’s impact, including the arrangement of the pit, was performed in a plane, nonlinear formulation by the finite element method (FEM). Numerical modeling of the system "base - foundations of the existing building - shoring construction" was performed using an elastic-plastic soil model with the Mohr-Coulomb strength criterion.